Feasibility, Acceptability, and Tolerability of Targeted Naltrexone for Nondependent Methamphetamine-Using and Binge-Drinking Men Who Have Sex with Men. (1st May 2016) - Santos, Glenn-Milo; Coffin, Phillip; Santos, Deirdre; Huffaker, Shannon; Matheson, Tim; Euren, Jason; DeMartini, Anna; Rowe, Christopher; Hahn, Judith A.; Vlahov, David; Vittinghoff, Eric; Batki, Steven L.
Abstract : Background: There are no effective pharmacologic strategies for nondependent methamphetamine (meth)-using and binge-drinking men who have sex with men (MSM) at high-risk for HIV. We sought to determine the feasibility of enrolling and retaining this population in a pharmacologic trial; the acceptability of pharmacotherapy study procedures; and the tolerability of targeted naltrexone versus placebo. Methods: Thirty meth-using and binge-drinking MSM were randomly assigned 1:1 to 50 mg naltrexone or placebo for 8 weeks for targeted administration (ie, during craving or in anticipation of meth or alcohol use). Substance use counseling and behavioral assessments were conducted every 2 weeks. Medication use was measured using WisePill dispensers. Results: Trial completion was 93%; visit completion rate was 95%. Mean weekly number of medication pills taken was 2.1 and was similar between arms. Participant satisfaction rate was 96%. There were neither serious adverse events nor differences in adverse event rates between arms. In exploratory intention-to-treat analyses, there were no differences in meth use and drinking. Naltrexone participants had greater reductions in serodiscordant receptive anal intercourse [incident rate ratio (IRR) = 0.15; 95% CI = 0.05 to 0.42] and serodiscordant condomless receptive anal intercourse (IRR = 0.11; 95% CI = 0.03 to 0.37), compared with placebo. In subgroup analyses among frequent meth users, naltrexone participants had greater reductions in meth-using days (IRR = 0.78; 95% CI = 0.62 to 0.99). In as-treated analyses, frequent study medication users in the naltrexone arm had greater reductions in binge drinking days (IRR = 0.72; 95% CI = 0.54 to 0.97). Conclusions: Targeted naltrexone is a feasible, acceptable, and tolerable intervention strategy for nondependent meth-using and binge-drinking MSM. Naltrexone was associated with significant sexual risk reductions; and for some individuals, naltrexone was associated with meth and binge-drinking reductions.